How Does the Measurement of Disability in Low Back Pain Map Unto the International Classification of Functioning, Disability and Health?: A Scoping Review of the Manual Medicine Literature. (April 2021) - Nicol, Richard; Yu, Hainan; Selb, Melissa; Prodinger, Birgit; Hartvigsen, Jan; Côté, Pierre
Abstract : Abstract: The objective of this study was to catalog items from instruments used to measure functioning, disability, and contextual factors in patients with low back pain treated with manual medicine (manipulation and mobilization) according to the International Classification of Functioning, Disability and Health. This catalog will be used to inform the development of an International Classification of Functioning, Disability and Health–based assessment schedule for low back pain patients treated with manual medicine. In this scoping review, we systematically searched MEDLINE, Embase, PsycINFO, and CINAHL. We identified instruments (questionnaires, clinical tests, single questions) used to measure functioning, disability, and contextual factors, extracted the relevant items, and then linked these items to the International Classification of Functioning, Disability and Health. We included 95 articles and identified 1510 meaningful concepts. All but 70 items were linked to the International Classification of Functioning, Disability and Health. Of the concepts linked to the International Classification of Functioning, Disability and Health, body functions accounted for 34.7%, body structures accounted for 0%, activities and participation accounted for 41%, environmental factors accounted for 3.6%, and personal factors accounted for 16%. Most items used to measure functioning and disability in low back pain patient treated with manual medicine focus on body functions, as well as activities and participation. The lack of measures that address environmental factors warrants further investigation. Abstract : Supplemental digital content is available in the text.